Control of Environmental Impacts through Licensing to Achieve Sustainable Development - Enggarani, Nuria Siswi (Universitas Muhammadiyah Surakarta, 2015)
Control of environmental impacts need to be implemented by maximally utilizing licensing instruments. Licensing becomes the supervisor and an instrument control of development program that can be implemented in accordance with applicable regulations. Moreover, in order to preserve the function and balance of the environment due to any national economic development as mandated by the Constitution Republic of Indonesia 1945, it should be held based on the principle of sustainable development that meets the needs of the present without undermining the ability of future generations to meet their needs with the people who live within the confines of a mutually supportive environment.